2001
DOI: 10.1094/pdis.2001.85.6.668
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Establishment of Infection on Grape Berries by Single Airborne Conidia ofBotrytis cinerea

Abstract: Table grapes (cv. Dauphine) at different phenological stages were dusted in a settling tower with dry conidia of Botrytis cinerea. The berries were incubated for periods of 3 to 96 h at high relative humidity (RH; ±93% RH, moist berries), or were covered with a film of water (wet berries). Germination of the solitary conidia, appressorium formation, stilbene and suberin induction by germlings, and germling viability were examined by fluorescence microscopy after each incubation period. Isolation and freezing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 45 publications
0
33
1
Order By: Relevance
“…Since B. cinerea incidence on paraquat medium was the result of infection after the termination of host resistance by the herbicide (Grindat & Pezet, 1994), infection levels would therefore provide a clear indication of the fungicide action in the absence of active host resistance. When studying B. cinerea infection on Kerssies medium, fungicidal action was masked by host resistance (Coertze & Holz, 1999;Coertze et al, 2001), which might have contributed to the variability of incidence data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since B. cinerea incidence on paraquat medium was the result of infection after the termination of host resistance by the herbicide (Grindat & Pezet, 1994), infection levels would therefore provide a clear indication of the fungicide action in the absence of active host resistance. When studying B. cinerea infection on Kerssies medium, fungicidal action was masked by host resistance (Coertze & Holz, 1999;Coertze et al, 2001), which might have contributed to the variability of incidence data.…”
Section: Discussionmentioning
confidence: 99%
“…The different isolation treatments provided conditions that facilitated the development of B. cinerea by conidia on the surface of bunch tissue, or by mycelia in the tissue, during the period of incubation. Previous studies (Coertze & Holz, 1999;Coertze et al, 2001;Gütschow, 2001) with grape bunch tissue on Kerssies medium showed that segments retained their active defense abilities and no superficial mycelial growth developed on the segments during the first five days of incubation. Hyphal growth usually occurred from cells underlying the cuticle into the medium after five days, which indicated direct penetration by conidia on the surface, and the development of mycelia from the host tissue during the incubation period.…”
Section: Assessment Of B Cinereamentioning
confidence: 92%
See 2 more Smart Citations
“…Infections of berries occur at temperature interval between 20 and 25 C and are accomplished by conidia. Germlings that developed from conidia enter grape berries through different pathways, namely through stigmata, pedicels, natural openings and wounds, or by direct penetration of the cuticle (Coertze et al, 2001;Holz et al, 2003). Conidia are deposited on berry surphace by air, rain or insects.…”
Section: Bunch Rot Of Grapes: High Standard Disease Of Grapevinementioning
confidence: 99%